2002
DOI: 10.4269/ajtmh.2002.67.102
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to dengue hemorrhagic fever in vietnam: evidence of an association with variation in the vitamin d receptor and Fc gamma receptor IIa genes.

Abstract: Abstract. Dengue is an increasingly important cause of morbidity and mortality in the tropics, with more than a billion people at risk each year. Immunologic enhancement is thought to contribute to disease pathogenesis. Only a very small proportion of infected individuals develop life-threatening dengue hemorrhagic fever (DHF). In a large casecontrol study with 400 DHF patients and 300 matched controls, we have assessed five polymorphic non-HLA host genetic factors that might influence susceptibility to DHF. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 44 publications
3
135
1
2
Order By: Relevance
“…90 The vitamin D receptor modulates the immune response by stimulating cell-mediated immunity and inhibiting lymphocyte proliferation; a polymorphism in the receptor appears to protect against severe dengue. 94 The Fc receptor mediates entry of antibody-coated DENV into target cells; the same study demonstrated that homozygotes for the arginine variant at position 131 of the Fc receptor gene may also be protected from severe disease. 94 This is perhaps because these homozygotes have less ability to opsonise IgG2 antibodies.…”
Section: Genetic Determinants Of Dengue Susceptibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…90 The vitamin D receptor modulates the immune response by stimulating cell-mediated immunity and inhibiting lymphocyte proliferation; a polymorphism in the receptor appears to protect against severe dengue. 94 The Fc receptor mediates entry of antibody-coated DENV into target cells; the same study demonstrated that homozygotes for the arginine variant at position 131 of the Fc receptor gene may also be protected from severe disease. 94 This is perhaps because these homozygotes have less ability to opsonise IgG2 antibodies.…”
Section: Genetic Determinants Of Dengue Susceptibilitymentioning
confidence: 99%
“…94 The Fc receptor mediates entry of antibody-coated DENV into target cells; the same study demonstrated that homozygotes for the arginine variant at position 131 of the Fc receptor gene may also be protected from severe disease. 94 This is perhaps because these homozygotes have less ability to opsonise IgG2 antibodies. There have been conflicting results from studies looking at polymorphisms in the TNF- gene -data from Vietnam did not show an association, whereas investigators in Venezuela reported a significantly increased prevalence of the TNF-308A allele in patients with severe dengue.…”
Section: Genetic Determinants Of Dengue Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Host factors that increase the risk of severe dengue disease include female sex, several human leukocyte antigen (HLA) class I alleles, a promoter variant of the DC-SIGN receptor gene, a single-nucleotide polymorphism in the tumour necrosis factor (TNF) gene and AB blood group [31][32][33][34][35][36] . Host factors that reduce the risk of severe disease during a second dengue infection include race, second or third degree malnutrition, and polymorphisms in the Fcγ receptor and vitamin D receptor genes [37][38][39][40][41][42] . Secondary dengue infections in adults can produce the classical DSS or severe disease complicated by haemorrhages.…”
Section: Dengue Virus Pathogenesismentioning
confidence: 99%
“…Warm and humid climate, population density, and housing aspects also influence disease outbreaks. Nevertheless, little information is available on the influence of genetic factors for dengue infection susceptibility (Loke et al 2002).…”
Section: Discussionmentioning
confidence: 99%